2021
DOI: 10.1371/journal.pone.0254553
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of infective endocarditis admission in adults: A population-based registry study in Finland

Abstract: Infective endocarditis (IE) is associated with high mortality. However, data on factors associated with length of stay (LOS) in hospital due to IE are scarce. In addition, long-term mortality of more than 1 year is inadequately known. In this large population-based study we investigated age and sex differences, temporal trends, and factors affecting the LOS in patients with IE and in-hospital, 1-year, 5-year and 10-year mortality of IE. Data on patients (≥18 years of age) admitted to hospital due to IE in Finl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
(112 reference statements)
2
12
1
Order By: Relevance
“…Along with comparing the incidence of IE between the sexes, it’s also been shown that there is a variation in the age at which each sex develops IE. Most patients with IE were between 60 and 79 years old, with an average of 62.2 years old [ 17 - 19 , 22 , 35 , 36 ]. Erichsen et al observed that the mean age of IE diagnosis in both sexes has increased steadily, but no study reports variations towards one sex [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Along with comparing the incidence of IE between the sexes, it’s also been shown that there is a variation in the age at which each sex develops IE. Most patients with IE were between 60 and 79 years old, with an average of 62.2 years old [ 17 - 19 , 22 , 35 , 36 ]. Erichsen et al observed that the mean age of IE diagnosis in both sexes has increased steadily, but no study reports variations towards one sex [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Becher et al observed that hypertension is the highest comorbidity associated with patients with a diagnosis of IE at up to 44.9% [ 17 ]. In comparing the sexes, four studies observed differences in their Charlson comorbidity index, but many others found differences [ 20 , 26 , 35 , 40 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a relative lack of data from low-and middle-income regions which can signi cantly affect the overall incidence of IE. A nationwide study from the United States (US) reported nearly half a million IE-related hospitalizations from 2000 to 2011 and a steady increase in its incidence [ [6][7][8][9][10][11] ]. The short-term mortality related to infective endocarditis has been estimated to be 10-24% [ 11 ].…”
Section: Introductionmentioning
confidence: 99%